EXTRALINGUISTIC ISSUES IN CROSS-CULTURAL COMMUNICATION: BODY LANGUAGE, TABOOS. (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: In this article, as we know, body language and taboos an inseparable part of nonverbal communication, plays an important role in foreign language learning and teaching. This article provides information on the use of body language and taboos and their meanings.